Analisis Pengaruh Penambahan Pektin Kulit Buah Naga (Hylocereus polyrhizus) Terhadap Pertumbuhan dan Efisiensi Pemanfaatan Pakan pada Ikan Jelawat (Leptobarbus hoevenii) - Susanti, Sari; Agustina; Nikhlani, Andi (Faculty of Science and Technology University Ibrahimy, 2026)
Pectin is a dietary fiber that encourages the growth of lactic acid bacteria to increase the growth and digestibility of fish feed. Pectin from fruit skin has the potential as a feed additive for fish in an effort to increase production. The purpose of this study was to analyze the effect of adding pectin from dragon fruit skin on the growth and feed utilization of eelfish. This study used a Completely Randomized Design (CRD) consisting of four treatments and three replications. Treatments with feeding and adding pectin at doses of 0; 5; 10 and 15 g/kg of feed. Eelfish measuring 9-10 cm as many as 15 fish/tub were kept in a container with a water volume of 40 L for 30 days and fed according to the treatment twice a day ad satiation. The results showed that pectin from dragon fruit skin with different doses in the feed given to eelfish showed a significant effect on absolute weight growth and protein efficiency ratio. The results of this study also showed that pectin with a dose of 5 g/kg feed produced the best value for absolute weight growth with an average of 2.80 g, specific growth rate with an average of 0.97%, feed conversion ratio with a value of 1.01, and protein efficiency ratio with a value of 2.48.